A profile of 23 indian patients with purpura fulminans: A retrospective, descriptive study - Sudip Kumar Ghosh; Debabrata Bandyopadhyay; Abhijit Dutta; P Esther Jane; Surajit Kumar Biswas (Wolters Kluwer Medknow Publications, 2020)
Background: Purpura fulminans (PF) is a potentially fatal uncommon disorder of intravascular thrombosis and is clinically characterized by rapidly progressive hemorrhagic infarction of the skin. Objective: To describe the clinical feature and outcome of a series of patients with PF. Materials and Methods: A descriptive study based on review of case records was carried out at a tertiary care hospital in Kolkata. Results: Twenty three consecutive cases seen over a period of 8 years were studied. The age range was 4 days to 78 years (mean 35.6 years) with a male to female ratio of 1:2.8. Hemorrhagic rash was the universal presenting symptom. Other major presenting features included pneumonia (26.1%), sudden-onset shock syndrome (21.7%), and urinary tract infection (17.4%). All patients presented with retiform purpura and lesional necrosis and 8 (34.8%) patients had associated peripheral gangrene. Nineteen (82.6%) patients had sepsis and 60.9% patients had vesiculo-bullous lesion. Pneumococcus was the most common (26.1%) pathogenic organism detected. The precise cause of PF could not be detected in two (8.7%) patients. One patient (4.3%) with neonatal PF had protein C deficiency. All patients had evidence of disseminated intravascular coagulation (DIC). One patient had to undergo a below knee surgical amputation and one patient had autoamputation of the digits. Ten (43.5%) patients succumbed to their illness. Seven of the 8 patients who had peripheral gangrene had a fatal outcome. Limitations: Relatively small sample size and a referral bias were a few limitations of the present study. Conclusion: The present study emphasizes that PF is a cutaneous marker of DIC. Association of peripheral gangrene, leukopenia and neutropenia may be the reason for the high mortality rate.